Functionalized lithium anodes for batteries

Functionalized lithium anodes, prepared by reacting lithium metal substrates with aromatic diazonium salts, address the stability issues of lithium metal anodes in Li-S batteries, resulting in improved cycle life and Coulomb efficiency.

JP7643666B6Active Publication Date: 2025-03-28ACONDICIONAMIENTO TARRASENSE +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021571553
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-30
Filing Date
2020-05-05
Publication Date
2025-03-28
Estimated Expiration
2040-05-05

AI Technical Summary

Technical Problem

Existing lithium-sulfur (Li-S) batteries face challenges with the stability of lithium metal anodes, leading to rapid capacity fading and adverse effects on cycle life due to dendrite growth and polysulfide shuttling.

Method used

A method for preparing functionalized lithium anodes by contacting a lithium metal substrate with an aromatic diazonium salt in an organic solvent, such as morpholine solvents with alkyl groups, to enhance physicochemical stability and prevent dendrite growth and polysulfide diffusion.

Benefits of technology

The functionalized lithium anodes demonstrate improved cycle life and Coulomb efficiency by reducing electrolyte consumption and blocking polysulfide shuttling, resulting in enhanced stability and performance of Li-S batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643666000003
    Figure 0007643666000003
  • Figure 0007643666000004
    Figure 0007643666000004
  • Figure 0007643666000005
    Figure 0007643666000005
Patent Text Reader

Abstract

The present invention relates to a functionalized lithium anode for batteries, which is obtained by a specific method using a diazonium salt. The present invention also relates to the use of the lithium anode in a cell, a cell comprising the lithium anode, the use of the cell in an electronic device, and an electronic device comprising the cell.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of batteries, in particular Li-S, Li-ion or Li-O 2 This relates to lithium negative electrodes for batteries. [Background technology]

[0002] Batteries are energy storage devices and their performance is highly demanded. There are various types of batteries, such as Ni-Cd, Ni-Zn, Ag-Zn, Li-ion, Li-O 2、 Lithium-iron-phosphate, Li-S.

[0003] In particular, Li-S batteries have received particular attention due to their fairly low cost and high theoretical specific capacity (1675 mA.h / g) and theoretical energy density (2500 W.h / kg).

[0004] A Li-S battery generally includes a positive electrode, a separator, an electrolyte, a negative electrode, and a current collector.

[0005] The positive electrode usually contains sulfur, a carbon-based material and a binder. The negative electrode is lithium metal and is usually separated from the positive electrode by a separator and an organic solvent-based electrolyte.

[0006] Non-Patent Document 1: Fotouhi et al., Lithium-Sulfur Battery Technology Readiness and Applications - A Review, Energies, 2017, 10, 1937 summarizes the operating principle of the Li-S battery, that is, during operation (discharge), solid sulfur from the positive electrode dissolves into the electrolyte, and S 8 (I) is formed. Liquid S 8 is then electrochemically reduced at the positive electrode to Li metal at the negative electrode. + ions, intermediate products, so-called lithium polysulfide (PS) species (Li 2 S x) is formed. Polysulfide species (Li 2 S x , 2 < x ≦ 8) are soluble in the liquid electrolyte and diffuse out from the positive electrode to the electrolyte / separator side. As discharge proceeds, the length of the polysulfide chain becomes shorter, which in turn affects the viscosity, fluidity and solubility of the Li 2 S x compound. At the end of discharge, S 8 is fully reduced to Li 2 S, and the negative electrode has the Li metal fully stripped off.

[0007] Looking at the prior art of Li-S batteries, Non-Patent Document 2: Zhang et al., Advances in lithium - sulfur batteries, Mat. Sci. Eng. R, 2017, 121, 1-29 discloses that the problems of lithium metal are well-known, namely strong reactivity, dendrite formation, and safety concerns. As a result, recently, attempts have been made to replace Li with another negative electrode selected from among the negative electrodes already used in Li-ion batteries, such as silicon-based negative electrodes.

[0008] Non-Patent Document 3: Kang et al., A review of recent developments in rechargeable lithium‐sulfur batteries, Nanoscale, 2016, 8, 16541-16588 is a review on rechargeable Li-S batteries, which covers the development of negative electrodes. The negative electrode is an essential component of a Li-S battery, and it is disclosed that if the negative electrode is unstable, the cycle life of the battery will be adversely affected with rapid capacity fading. Several beneficial methods that need to be considered for protecting the lithium negative electrode of a Li-S battery are disclosed, namely a protective layer for the negative electrode (e.g., multilayer graphene, solid electrolyte interface (SEI)), a composite (e.g., ternary composite Si-C-Li), a pre-lithiated negative electrode (e.g., pre-lithiated Si, graphene filled with Li in pores), or a Li-ion insertion material as the negative electrode (e.g., carbon, Si-based, Sn-based).

[0009] Non-Patent Document 4: Cheng et al., Toward Safe Lithium Metal Anode in Rechargeable Batteries: A Review, Chem. Rev., 2017, 117, 10403-10473, discloses several approaches to protect Li anodes, namely solid electrolyte interfaces (electrochemical pretreatment, chemical pretreatment, physical pretreatment), lithiophilic matrix, and artificial formation of conductive matrix.

[0010] Non-Patent Document 5: Luo et al., A dual-functional polymer coating on a lithium anode for suppressing dendrite growth and polysulfide shuttling in Li-S batteries, Chem. Comm., 2017, 53, 963-966, discloses a lithium anode coated with a polymer blend consisting of Nafion® and polyvinylidene fluoride (PVDF), which shows improved coulombic efficiency along with substantial enhancement of rate performance and cyclability of Li-S prototype batteries with high S content cathodes.

[0011] Non-Patent Document 6: Manthiram et al., Rechargeable Lithium-Sulfur Batteries, Chem. Rev., 2014, 114, 11751-11787 discloses that the negative electrode is an essential part of the Li-S battery because its stability determines the long-term cycle life of the Li-S battery. Furthermore, it discloses that the reliability of the lithium metal negative electrode is highly dependent on the stability of its passivation layer, which can be improved by changing the electrolyte solvent and introducing additives. As an alternative, silicon-based and carbon-based negative electrodes containing lithium are disclosed.

[0012] Non-Patent Document 7: Ma et al., Enhanced cycle performance of a Li-S battery based on a protected lithium anode, J. Mater. Chem. A, 2014, 2, 19355-19359, discloses a conductive polymer layer prepared on the surface of a lithium anode as a protective layer for Li-S batteries. It not only effectively prevents the corrosion reaction between the lithium anode and lithium polysulfide, but also inhibits Li dendrite growth. The polymer is prepared from PEDOT and PEG (poly(3,4-ethylenedioxythiophene)-co-poly(ethylene glycol)). The protective coating was prepared by immersing lithium metal into a polymer solution.

[0013] Patent document 1: PCT International Application WO-A-2016 / 083271 discloses sulfonated fluororesins as coatings for lithium electrodes for Li-S batteries.

[0014] Non-Patent Document 8: Song et al., Ionomer-Liquid Electrolyte Hybrid Ionic Conductor for High Cycling Stability of Lithium Metal Electrodes, Sci. Rep., 2015, 5, 14458 discloses a highly ionically conductive ionomer / liquid electrolyte hybrid layer firmly laminated to a Li metal electrode, which has a current density of 10 mA / cm 2 The hybrid layer was fabricated by depositing a few microns thick Nafion layer on a Li metal electrode, followed by 1M LiPF 6 It is disclosed to be prepared by immersion in an ethylene carbonate / diethyl carbonate (1 / 1) electrolyte.

[0015] Non-Patent Document 9: Kazyak et al., Improved Cycle Life and Stability of Lithium Metal Anodes through Ultrathin Atomic Layer Deposition Surface Treatments, Chem. 2 O 3 It is disclosed that lithium metal anodes are treated with a 5000 vol.

[0016] Non-Patent Document 10: Wu et al., A Trimethylsilyl Chloride Modified Li Anode for Enhanced Performance of Li-S Cells, ACS Appl. Mater. Interfaces, 2016, 8, 16386-16395, discloses a method to improve the lithium anode for Li-S cells by sequentially exposing lithium foil to tetrahydrofuran solvent, oxygen atmosphere, and chlorotrimethylsilane liquid. XPS data show that Li-SiMe 3 rather than Li-O-SiMe 3 It is confirmed that the above-mentioned reversible discharge capacity and higher coulombic efficiency can be achieved.

[0017] Non-Patent Document 11: Fan et al., Advanced chemical strategies for lithium-sulfur batteries: A review, Green Energy Environ., 2018, 3, 2-19 discloses that the performance of Li-S batteries is still far from theoretical predictions, which is due to the inherent insulation of sulfur, the shuttling of soluble polysulfides, swelling of the cathode, and the formation of lithium dendrites. This review mainly discusses recent advances in chemical absorption to improve the performance of Li-S batteries by introducing functional groups (oxygen, nitrogen, boron, etc.) and chemical additives (metals, polymers, etc.) into the carbon structure and how these foreign guests immobilize the dissolved polysulfides.

[0018] Non-Patent Document 12: Zhao et al., A review on anode for lithium-sulfur batteries: Progress and Prospects, Chem. Eng. J., 2018, 347, 343-365, discloses a comprehensive review of various strategies to enhance the anode stability of Li-S batteries, including improving the electrolyte and current collector, adopting artificial protective films, and finding another anode to replace the lithium anode. Several alternatives for protecting the lithium anode have been disclosed, namely, the formation of a solid electrolyte interface using electrolyte additives, artificial SEI films (e.g., by direct coating, magnetron sputtering, chemical coating, chemical grafting, chemical vapor deposition), sandwich technology, compound technology (e.g., C-Li, Si-Li, Si-C-Li, Sn-C-Li), and the use of non-lithium anodes (e.g., C, Si, metal alloys).

[0019] Non-Patent Document 13: Cheng et al., Review-Li Metal Anode in Working Lithium-Sulfur Batteries, J. Electrochem. Soc., 2018, 165(1), A6058 - A6072 discloses that the application of lithium-sulfur batteries is challenged by several obstacles, including low sulfur utilization and poor life, which are partly due to the shuttle of lithium polysulfides and lithium dendrite growth in working lithium-sulfur batteries. Considering the influence of Li polysulfides, several strategies have been proposed to protect the Li metal anode, such as electrolyte additives, artificial solid electrolyte interface (SEI), solid-type electrolytes, and structured composite lithium anodes. Furthermore, surface coating is a facile and cost-effective method to deposit a protective layer on the Li metal anode, which can be conveniently applied to practical Li-S batteries, and the coating material is Al-based. 2 O 3 , carbon, some polymers and some alloys are disclosed.

[0020] Therefore, despite the different proposals available in the prior art, there remains a need to provide new lithium anodes that are effective in Li-S batteries. [Prior art documents] [Non-patent literature]

[0021] [Non-Patent Document 1] A Review, Energies, 2017, 10, 1937 [Non-Patent Document 2] Mat. Sci. Eng. R, 2017, 121, 1-29 [Non-Patent Document 3] Nanoscale, 2016, 8, 16541-16588 [Non-Patent Document 4] A Review, Chem. Rev., 2017, 117, 10403-10473 [Non-Patent Document 5] Chem. Comm., 2017, 53, 963-966 [Non-Patent Document 6] Chem. Rev., 2014, 114, 11751-11787 [Non-Patent Document 7] J. Mater. Chem. A, 2014, 2, 19355-19359 [Non-Patent Document 8] Sci. Rep., 2015, 5, 14458 [Non-Patent Document 9] Chem. Mater., 2015, 27(18), 6457-6452 [Non-Patent Document 10] ACS Appl. Mater. Interfaces, 2016, 8, 16386-16395 [Non-Patent Document 11] A review, Green Energy Environ., 2018, 3, 2-19 [Non-Patent Document 12] Chem. Eng. J., 2018, 347, 343-365 [Non-Patent Document 13] J. Electrochem. Soc., 2018, 165(1), A6058-A6072 [Patent documents]

[0022] [Patent Document 1] WO2016 / 083271A Summary of the Invention [Problem to be solved by the invention]

[0023] The object of the present invention is a method for preparing a functionalized lithium anode for a battery.

[0024] Another aspect of the invention relates to a negative electrode obtainable by said method.

[0025] Another aspect of the invention relates to the use of the negative electrode in a cell.

[0026] Another aspect of the invention relates to a cell including the negative electrode.

[0027] Another aspect of the invention relates to the use of the cells in electronic devices.

[0028] Another aspect of the invention relates to an electronic device including the cell. [Brief description of the drawings]

[0029] [Figure 1] 1 shows an assembly used to test a lithium anode functionalized according to the method of the present invention versus a non-functionalized lithium anode, the assembly including the following elements: a stainless steel cap, a lithium metal anode, a separator, a carbon-sulfur cathode, a stainless steel spacer, and a stainless steel cap. [Diagram 2] In Figure 2 the results of the galvanostatic tests carried out in Example 10 with a functionalized lithium anode (Δ) according to Example 1 and with a non-functionalized lithium anode (O) are shown, with the discharge capacity expressed in mAh / g on the ordinate and the number of cycles on the abscissa. [Diagram 3] In Figure 3 the results of the galvanostatic tests carried out in Example 10 with a functionalized lithium anode (Δ) according to Example 1 and with a non-functionalized lithium anode (O) are shown, with the coulombic efficiency (CE) expressed in % on the ordinate and the number of cycles on the abscissa. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The subject of the present invention is ethers, enol ethers, 0-4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0-4 C 1 -C 4A method for preparing a functionalized lithium anode comprises contacting a lithium metal substrate with an aromatic diazonium salt in an organic solvent selected from alkyl group-containing morpholine solvents.

[0031] The inventors of the present invention have developed a method for preparing functionalized lithium anodes, by reaction with diazonium salts, that improve both cycle life and coulombic efficiency when incorporated into electrochemical cells (hereinafter "cells"), particularly Li-S cells. It has been surprisingly found that reduction of diazonium salts on the lithium metal surface provides the lithium anodes with enhanced physicochemical stability leading to improved battery efficiency and extended life.

[0032] With respect to other existing techniques / treatments proposed to protect Li anodes, the attachment of an organic layer to lithium by reduction of a diazonium salt has several advantages in view of dendrite growth and other deleterious interaction processes (e.g. diffusion of polysulfides to the anode in Li-S batteries), one of which is the undoubtedly strong nature of the (covalent) bond established between the immobilized organic layer and the lithium substrate, which constitutes a convenient means of immobilizing a stable covalent film onto the lithium. It appears to be a method of choice for the strong covalent attachment of polymer chains to the surface forming ultra-thin films (thicknesses can vary from monolayers to microns). It confers chemical, mechanical and thermal stability to the organically modified lithium anode that overwhelms those of other coatings cast via other methods. The result is therefore a more resistant and durable protective coating that can withstand the harsh conditions of frequent operation.

[0033] The reduction of aryl diazonium salts on lithium anodes also constitutes a versatile method, i.e., an almost unlimited number of diazonium salts can be used, either commercially available or generated in situ via aniline derivatives. This allows the grafting of a wide range of organic molecules and at the same time allows tuning of the surface properties of Li. In addition to this, various solvents can be used to graft these organic layers onto lithium, such as toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine, 1,4-dioxane, and combinations thereof, which further enhance the applicability of the method. Thus, by using a suitable solvent, the method of the present invention allows the grafting of diazonium precursors onto lithium metal substrates without parasitic / secondary reactions between the solvent and the lithium metal substrate. Preferably, the solvent is non-polar. The solvent can be an ether, an enol ether, an ether with 0-4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0-4 C 1 -C 4 In a preferred embodiment, the solvent is selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine and 1,4 dioxane.

[0034] It is also a relatively simple and effective technique to perform, and can be easily achieved by application of a potential step in the presence of inexpensive reagents, either spontaneously or via electrochemical induction. This directly contrasts with more complex schemes and expensive techniques used today to perform lithium surface derivatization to achieve a similar goal, i.e. to protect Li anodes from polysulfide diffusion and other deleterious interaction processes (e.g., dendrite growth) within the Li-S electrons.

[0035] Throughout this specification and the claims, the singular references preceded by the articles "a" or "the" are understood to broadly include plural references as well, unless the context clearly indicates to the contrary.

[0036] In the context of the present invention, the term "approximately" referring to a given value is understood to allow for a certain variation in said value, generally + / - 5%.

[0037] Descriptions of aspects of the invention using terms such as "comprising," "having," "including," or "containing" in connection with elements are intended to provide support for similar aspects of the invention, and "consisting of," "consists essentially of," or "substantially comprises" are intended to provide support for the specific elements unless otherwise stated or clearly contradicted by context.

[0038] The ranges disclosed in the detailed description of the invention herein include both the upper and lower limits.

[0039] Lithium Metal Substrate Lithium metal substrates suitable for preparing lithium anodes are available in chip form, for example from MTI Corp. In a preferred embodiment, the lithium metal substrate is of high purity, typically 99.9%, and of various shapes, thicknesses and surfaces, depending on the type and construction of the cell, in which the anode is placed, for example, in a coin cell or pouch cell.

[0040] Diazonium Salts The lithium anode of the present invention is a compound having a structure such as an ether, an enol ether, or 0 to 4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0-4 C 1 -C 4The functionalization is carried out using reaction with an aromatic diazonium salt in a solvent selected from alkyl group bearing morpholine solvents, preferably in a solvent selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine, and 1,4 dioxane.

[0041] The diazonium salts are generally prepared from the corresponding anilines, or in some cases are commercially available as such.

[0042] The diazonium salts, in a preferred embodiment, are prepared from the corresponding anilines in the presence of a nitrosating agent, e.g., alkyl nitrites such as methyl nitrite, isopropyl nitrite, tert-butyl nitrite, amyl nitrite, or isoamyl nitrite, prior to reaction with the lithium anode, without the need for isolation or purification.

[0043] The diazonium salt, once synthesized, can be isolated in another preferred embodiment or a commercially available diazonium salt can be used. In that embodiment, the diazonium salt is dissolved prior to reaction with the lithium negative electrode. In a more preferred embodiment, the diazonium salt is prepared or dissolved in a vessel, followed by introduction of the lithium negative electrode into the vessel for functionalization.

[0044] The diazonium salt suitable for use in the present patent application method is not limited by the substituents present on the phenyl group, but may be, for example, 4-nitrobenzenediazonium tetrafluoroborate, 4-bromobenzenediazonium tetrafluoroborate, and 3,5-dichlorophenyldiazonium tetrafluoroborate, which are commercially available (Sigma-Aldrich), or 4-propargyloxybenzenediazonium tetrafluoroborate, which is disclosed in "Jin et.al., Click Chemistry on Solution-Dispersed Graphene and Monolayer CVD Graphene, Chem. Mat., 2011, 23 (14), 3362-3370". Halide diazonium salts may also be used to post-functionalize the laminate separator using nucleophilic substitution.

[0045] 4-Propargyloxybenzenediazonium tetrafluoroborate is suitable for post-functionalization of lithium anodes using click chemistry as disclosed in Jin et al., supra.

[0046] Anilines suitable for use in the process of the present patent application are, for example, 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)-aniline and 4-aminophenethyl alcohol, which are commercially available (Sigma-Aldrich).

[0047] The conversion of anilines to diazonium salts is described, for example, in MB Smith, J. March, March's Advanced Organic Chemistry (5 thed.), John Wiley & Sons, New York, 2001 (ISBN: 0-471-58589-0). In the reaction, aniline is treated with nitrous acid or a combination of sodium nitrite and hydrochloric acid, which generates nitrous acid or an equivalent compound, such as an alkyl nitrite, as disclosed in F. Csende, Alkyl Nitrates Valuable Reagents in Organic Synthesis, Mini-Rev. Org. Chem., 2015, 12, 127-148, as a suitable solvent, preferably a deoxygenated solvent.

[0048] The anion of the diazonium salt depends on the acid used in the diazotization reaction. Generally, the anion is hydrochloride, hydrobromide or tetrafluoroborate.

[0049] The aniline, in a preferred embodiment, is reacted with tert-butyl nitrite in a non-aqueous environment such as a deoxygenated solvent selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine, and 1,4-dioxane.

[0050] The diazonium salt is in a preferred embodiment selected from the group of diazonium salts comprising 4-nitrobenzenediazonium tetrafluoroborate, 4-bromobenzenediazonium tetrafluoroborate, 3,5-dichlorophenyldiazonium tetrafluoroborate and 4-propargyloxybenzenediazonium tetrafluoroborate, and the group of diazonium salts comprising 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline and 4-aminophenethyl alcohol. The lithium anode is in a preferred embodiment functionalized with a diazonium salt derived from 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline and 4-aminophenethyl alcohol, more preferably 3,5-bis(trifluoromethyl)aniline.

[0051] Functionalization Reaction A method for functionalizing the lithium anode involves reacting the lithium anode with an aromatic diazonium salt.

[0052] The functionalization reaction may be carried out electrochemically or chemically.

[0053] The reaction is, in a preferred embodiment, carried out electrochemically.

[0054] The reaction is, in another preferred embodiment, carried out chemically.

[0055] The reaction is usually carried out at room temperature, but depending on the solvent and the stability of the diazonium salt, it can be carried out at a temperature between 0° C. and 130° C. The reaction is preferably carried out at room temperature.

[0056] The electrochemical reaction of the diazonium salt can be carried out by either cyclic voltammetry or potential step approaches, which provide a high degree of control over the amount of material deposited. To achieve diazonium electroreduction, extremely low reduction potentials are required, typically 0 V (vs. Li / Li + ), and preferably the reduction potential is -1 V (vs. Li / Li + ) Because of the electron-withdrawing power of the diazonium group, only a low potential is required to generate the radical.

[0057] The chemical functionalization of the lithium negative electrode is carried out in a diazonium salt solution prepared in situ from the corresponding aniline compound or simply by dissolving a diazonium salt. The diazonium salt can be prepared and isolated or can be commercially available. The solvent can be an ether, an enol ether, or an amine having 0 to 4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0-4 C 1 -C 4The alkyl group-bearing morpholine solvent is preferably selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine and 1,4-dioxane. The solvent is preferably selected from toluene, tetrahydrofuran and 3,4-dihydro-2H-pyran. The reaction is generally complete after 30 minutes.

[0058] After the reaction, the method of preparing a functionalized lithium anode includes washing with the solvent used for functionalization and additional solvents of different polarity, acetonitrile and toluene, to reduce adsorption of the diazonium salt to the lithium surface.

[0059] Functionalized Lithium Anodes Another aspect of the present invention relates to functionalized lithium anodes obtainable by the process of the present invention.

[0060] The functionalized lithium anode comprises halo, -SC bonded to the surface of the lithium. 1 -C 6 Alkyl, -OH, Fluoro(C 1 -C 10 ) Alkyl, C 1 -C 5 Alkyl, -(C 1 -C 5 Alkyl)-OH, NO 2 The organic group includes an aromatic diazonium salt optionally substituted with 1 to 5 functional groups independently selected from , CN, and propargyloxy.

[0061] The lithium anode, in a preferred embodiment, comprises a substituted phenyl group attached to the surface of the lithium, more preferably the phenyl group is derived from a diazonium salt selected from the group comprising 4-nitrobenzenediazonium tetrafluoroborate, 4-bromobenzenediazonium tetrafluoroborate, 3,5-dichlorophenyldiazonium tetrafluoroborate and 4-propargyloxybenzenediazonium tetrafluoroborate, or a diazonium salt derived from an aniline selected from the group comprising 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline and 4-aminophenethyl alcohol.

[0062] Thus, the phenyl group attached to the surface of the lithium negative electrode is preferably selected from 4-nitrophenyl, 4-bromophenyl, 3,5-dichlorophenyl, 4-propargyloxyphenyl, 3,5-bis(trifluoromethyl)phenyl, 4-(heptadecafluorooctyl)phenyl, 4-phenethyl alcohol and 3-(methylthio)phenyl. In a preferred embodiment, the substituted phenyl group is selected from 3,5-bis(trifluoromethyl)phenyl, 4-(heptadecafluorooctyl) and 4-phenethyl alcohol, more preferably 3,5-bis(trifluoromethyl)phenyl.

[0063] X-ray photoelectron spectroscopy (XPS) confirms the functionalization that occurs on the surface of the lithium anode. The functionalization is the result of covalent bonding of the phenyl groups with the lithium surface resulting from homolytic dediazonation of the diazonium cation of the diazonium salt. This functionalization is maintained even after ultrasonic cleaning with different solvents, which confirms the strength and stability of the attachment.

[0064] Cells and Electronic Devices Another aspect of the invention is the use of functionalized lithium anodes in Li-S cells, Li-ion cells, and Li-O 2 Regarding use in cells.

[0065] The functionalized lithium anodes are suitable for use in Li-S cells, Li-ion cells and Li-O cells. 2 The present invention is suitable for incorporation into Li-S coin cells, Li-ion coin cells, and Li-O coin cells. In a preferred embodiment, it is used in Li-S coin cells. In another preferred embodiment, it is used in Li-S coin cells, Li-ion coin cells, and Li-O coin cells. 2 It is suitable for incorporation into coin cells, and in a more preferred embodiment, it is used in a Li-S coin cell.

[0066] A Li-S cell, such as a CR2016 coin cell, typically contains the following elements, as shown in Figure 1: 1) Stainless steel cap 2) Lithium metal anode 3) Separator 4) Carbon-sulfur cathode 5) Stainless steel spacer 6) Stainless steel cap Includes.

[0067] The cell further comprises an electrolyte, which in a preferred embodiment is 1,2-dimethoxyethane (DME), 1,3-dioxane (DOL), bis(trifluoromethylsulfonylamine) lithium salt LiTFSI, and LiNO 3 It consists of a combination of:

[0068] Other electrolytes based on lithium salt solutions, such as lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), LiCF 3 SO 3Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) can also be used in non-aqueous solvents such as TEGDME, 1,2-dimethoxyethane (DME), 1,3-dioxane (DOL), diglyme (DG), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), 2-ethoxyethyl ether (EEE), triglyme, poly(ethylene glycol) dimethyl ether (PEGDME), and combinations thereof. 6 The use of room temperature ionic liquid (RTIL) electrolytes such as 0.5M LiCF in DME / DOL solvent has also been demonstrated. 3 SO 3 or 0.5M LiPF 6 It has been reported as an additive to liquid electrolytes such as

[0069] As shown in Example 10 and Figures 2 and 3, the functionalized lithium anode according to the present invention shows both improved cell cycle life and coulombic efficiency with lower electrolyte depletion, where polysulfide shuttle is prevented, which is a result of the enhanced lithium interfacial stability provided by functionalization using diazonium reduction.

[0070] Thus, the advantages of the functionalized lithium anode of the present patent application over the prior art are clear.

[0071] In another aspect of the invention, a Li-S cell, a Li-ion cell or a Li-O cell comprising the lithium negative electrode is 2 It relates to a cell, preferably a Li-S cell.

[0072] In another aspect of the invention, the Li-S cell, Li-ion cell or Li-O 2 The present invention relates to the use of cells, preferably Li-S cells, in electronic devices.

[0073] Common electronic devices containing such cells are, for example, powered watches (both digital and analog), back-up power sources for real-time clocks in personal computers, laser pointers, small LED flashlights, solar / powered candles, LED bicycle headlights and taillights, pocket computers, hearing aids, electronic toys, heart rate monitors, digital thermometers and digital altimeters.

[0074] The present invention includes the following embodiments: 1. Ethers, enol ethers, 0-4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0-4 C 1 -C 4 A method for preparing a functionalized lithium anode comprising contacting a lithium metal substrate with an aromatic diazonium salt in an organic solvent selected from alkyl group-containing morpholine solvents.

[0075] 2. The method according to claim 1, wherein the solvent is selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine and 1,4 dioxane.

[0076] 3. The method of claim 1, wherein the lithium metal substrate is in the form of a chip.

[0077] 4. The method of any one of the preceding claims, wherein the diazonium salt is prepared from the corresponding aniline prior to reaction with the lithium anode.

[0078] 5. The method of any one of the preceding embodiments, wherein the diazonium salt is dissolved prior to reaction with the lithium negative electrode.

[0079] 6. The method according to any one of the preceding claims, characterized in that the diazonium salt is prepared or dissolved in a vessel, followed by introduction of the lithium anode and functionalization.

[0080] 7. The method according to any one of the preceding claims, characterized in that the diazonium salt is selected from the group of diazonium salts comprising 4-nitrobenzenediazonium tetrafluoroborate, 4-bromobenzenediazonium tetrafluoroborate, 3,5-dichlorophenyldiazonium tetrafluoroborate, and 4-propargyloxybenzenediazonium tetrafluoroborate, and from the group of diazonium salts comprising 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline, and 4-aminophenethyl alcohol.

[0081] 8. The method of embodiment 7, wherein the lithium negative electrode is functionalized with a diazonium salt derived from 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline, and 4-aminophenethyl alcohol.

[0082] 9. The method of embodiment 7, wherein the lithium negative electrode is functionalized with a diazonium salt derived from 3,5-bis(trifluoromethyl)aniline.

[0083] 10. The method according to any one of the preceding embodiments, characterized in that the functionalization reaction is carried out electrochemically or chemically.

[0084] 11. The method of claim 10, wherein the functionalization reaction is carried out electrochemically.

[0085] 12. The method of claim 10, wherein the functionalization reaction is carried out chemically.

[0086] 13. A functionalized lithium anode obtained by the method according to any one of the preceding claims.

[0087] 14. The functionalized lithium anode of embodiment 13, comprising an organic group attached to a surface of the lithium that is derived from an aromatic diazonium salt optionally substituted with a functional group.

[0088] 15. The functionalized lithium anode of embodiment 14, comprising a substituted phenyl group bonded to a surface of the lithium.

[0089] 16. The functionalized lithium anode of embodiment 15, wherein the phenyl groups attached to the surface of the lithium anode are selected from the group consisting of 4-nitrophenyl, 4-bromophenyl, 3,5-dichlorophenyl, 4-propargyloxyphenyl, 3,5-bis(trifluoromethyl)phenyl, 4-(heptadecafluorooctyl)phenyl, 4-phenethyl alcohol, and 3-(methylthio)phenyl.

[0090] 17. The functionalized lithium anode of embodiment 16, wherein the phenyl groups attached to the surface of the lithium anode are selected from a 3,5-bis(trifluoromethyl)phenyl group, a 4-(heptadecafluorooctyl) group, and a 4-phenethyl alcohol group.

[0091] 18. The functionalized lithium anode of embodiment 17, wherein the substituted phenyl group is a 3,5-bis(trifluoromethyl)phenyl group.

[0092] 19. A Li-S cell, Li-ion cell or Li-O cell comprising the functionalized lithium anode of any one of embodiments 13 to 18. 2 Use in cells selected from cells.

[0093] 20. The use of the functionalized lithium anode of embodiment 19 in a Li-S cell.

[0094] 21. A Li-S coin cell, Li-ion coin cell, or Li-O coin cell comprising the functionalized lithium negative electrode according to any one of the embodiments 13 to 18.2 Use in cells selected from coin cells.

[0095] 22. Use of the functionalized lithium anode of embodiment 21 in a Li-S coin cell.

[0096] 23. A Li-S cell, Li-ion cell or Li-O cell comprising a functionalized lithium anode according to any one of embodiments 13 to 18. 2 The cell selected from the cell.

[0097] 24. The cell of claim 23, wherein the cell is a Li-S cell.

[0098] 25. Use of a cell according to embodiment 23 or 24 in an electronic device.

[0099] 26. An electronic device comprising a cell according to any one of claims 23 to 24. EXAMPLES

[0100] Example 1: Chemical functionalization of lithium anodes Inside the glove box, remove the lithium chip (approximately 1.5 cm 2 , corresponding to 44 mg) was washed with n-pentane (3 min) and dried. Afterwards, a 3,5-bis(trifluoromethyl)diazonium salt solution (10 mM) was prepared by dissolving 3,5-bis(trifluoromethyl)aniline in dry toluene. An excess of tert-butyl nitrite was added to the diazonium salt (30 mM) and the solution was stirred for 30 min. Lithium chips were then added to the diazonium solution and stirred for 30 min. Finally, the chips were washed with toluene, the functionalization solvent and acetonitrile and dried.

[0101] X-ray photoelectron spectroscopy confirmed the occurrence of functional groups on the lithium surface by the presence of an intense peak in the spectrum assigned to the F1s binding energy, which was not observed in the spectrum corresponding to a non-functionalized lithium anode.

[0102] Examples 2-9: Chemical and electrochemical functionalization of lithium anodes According to the factors shown in Table I, 2 3 The functionalized negative electrodes were prepared by factorial design.

[0103] [Table I]

[0104] The experiments were carried out according to the layout shown in Table II. [Table II]

[0105] The reaction using 4-aminophenethyl alcohol (119 mg), which is a precursor of the diazonium salt, was carried out using anhydrous tetrahydrofuran (THF) as a solvent.

[0106] The reaction using the diazonium salt precursor (4-heptadecafluorooctyl)aniline (409 mg) was carried out using anhydrous 3,4-dihydro-2H-pyran as a solvent.

[0107] Chemical functionalization was carried out following a procedure substantially equivalent to that disclosed in Example 1.

[0108] The lithium chips were washed with n-pentane (3 min) and dried. The lithium chips were then placed in the diazonium salt solution (previously stirred for 30 min) and charged to -1 V (vs. Li / Li + Electrochemical functionalization was carried out by applying a potential of 0.01V for 30 min. The lithium chip was the working electrode, the Pt wire was the counter electrode, and the lithium wire was the reference electrode.

[0109] Finally, depending on the diazonium salt precursor, the Li chip was rinsed with either THF or 3,4-dihydro-2H-pyran as well as different polar solvents (toluene and acetonitrile) to reduce the adsorption of the diazonium salt onto the Li surface.

[0110] X-ray photoelectron spectroscopy confirmed that functionalization had occurred on the lithium surface in all four samples.

[0111] In the case of functionalization with 4-aminophenethyl alcohol (Examples 2, 4, 6 and 8), the main difference from the non-functionalized lithium anode is - Excess (%) of C1sII attributable to the CO environment (BE=287ev) - Excess (%) of O1sII (BE=534ev) attributable to the presence of OH groups (shoulder on the high binding energy side of the O1s peak) - C1sII (CO) / O1sII (OH) ratio ≒ 1 (according to the C / OH ratio for the C-O-H bonds), compared to 3.8 for pristine Li It was.

[0112] In the case of functionalization with (4-heptadecafluorooctyl)aniline (Examples 3, 5, 7 and 9), the main difference from the non-functionalized lithium anode is - Excess (%) attributable to FC fluorocarbon bonds F1s (687ev) and (690eV) - Excess (%) of C1s corresponding to CF (293 eV) It was.

[0113] Example 10: Galvanostatic testing of Li / S cells containing functionalized lithium anodes Galvanostatic testing of functionalized lithium anodes prepared according to the procedure disclosed in Example 1 and non-functionalized lithium anodes was carried out in a Li / S battery (CR2016-type coin cell) containing the following elements as shown in FIG. 1) Stainless steel cap (diameter 20 mm, thickness 1.6 mm) 2) Lithium metal anode (99.9% lithium chip, diameter 15.6 mm, thickness 0.25 mm) 3) Separator (Celgard® 2500) 4) 2.5mAh.cm containing 70% sulfur, 15% Ketjenblack carbon and 15% PEO-2 Sulfur / carbon based cathode 5) Stainless steel spacer (2 discs: diameter 16.7 mm, thickness 1 mm and 0.2 mm respectively) 6) Stainless steel cap (diameter 20 mm, thickness 1.6 mm)

[0114] 1:1 (v / v) dimethoxyethane:dioxane, 1M LiTFSI, 0.2M LiNO 3 The separator was immersed in an ether-based electrolyte of

[0115] The cells were cycled between 1.9 and 2.6 V at C / 5 with no depth of discharge (DOD) / capacity limitations. 1300 mA / g was used as 1C.

[0116] The coulombic efficiency of both lithium anodes was recorded and plotted against cycle number. The results are shown in Figure 2. Better coulombic efficiency was observed for the functionalized lithium anode (Δ) compared to the non-functionalized lithium anode (Ο). In fact, it can be seen that a higher coulombic efficiency was maintained in the cell containing the functionalized lithium anode, which indicates a lower depletion of the electrolyte.

[0117] The discharge capacity of both lithium anodes was recorded and plotted against the cycle number. The results are shown in Figure 3. The observed capacity values ​​were observed to be quite similar for both cells up to 120 cycles. Although a progressive drop was observed in all cases thereafter, it is clear that the performance of the cell containing the functionalized lithium anode (Δ) was better, exhibiting a higher discharge capacity along with a better coulombic efficiency (Figure 2). Thus, a better performance of the functionalized lithium anode (Δ) was observed as compared to the non-functionalized lithium anode (O) upon increasing cycle number.

[0118] The functionalized lithium negative electrodes according to the present invention have shown improvements in both cycle life and coulombic efficiency of electrochemical cells due to lower electrolyte depletion, where polysulfide shuttle is prevented, which is a result of the enhanced lithium interfacial stability provided by functionalization with diazonium salts.

Claims

1. Ethers, enol ethers, 0-4 C 1 -C 4 Aromatic hydrocarbons with alkyl groups or 0 to 4 C 1 -C 4 A method for preparing a functionalized lithium anode comprising contacting a lithium metal substrate with an aromatic diazonium salt in an organic solvent selected from alkyl group-containing morpholine solvents.

2. 2. The method according to claim 1, characterized in that the solvent is selected from toluene, tetrahydrofuran, 3,4-dihydro-2H-pyran, 4-ethylmorpholine, and 1,4 dioxane.

3. 3. The method of claim 1 or 2, wherein the lithium metal substrate is in the form of a chip.

4. A method according to any one of claims 1 to 3, characterized in that the diazonium salt is prepared from the corresponding aniline prior to reaction with the lithium metal substrate.

5. A method according to any one of claims 1 to 4, characterized in that the diazonium salt is dissolved prior to reaction with the lithium metal substrate.

6. 6. A method according to claim 4 or 5, characterized in that the diazonium salt is prepared or dissolved in a vessel, and then the lithium metal substrate is introduced into the vessel to effect functionalization.

7. 7. The method according to any one of claims 1 to 6, characterized in that the diazonium salt is selected from the group of diazonium salts comprising 4-nitrobenzenediazonium tetrafluoroborate, 4-bromobenzenediazonium tetrafluoroborate, 3,5-dichlorophenyldiazonium tetrafluoroborate, and 4-propargyloxybenzenediazonium tetrafluoroborate, and from the group of anilines comprising 3,5-bis(trifluoromethyl)aniline, 4-(heptadecafluorooctyl)aniline, and 4-aminophenethyl alcohol.

8. The method according to any one of claims 1 to 7, characterized in that the functionalization reaction is carried out electrochemically or chemically.

9. A functionalized lithium anode obtainable by the method according to any one of claims 1 to 8.

10. 10. The functionalized lithium anode of claim 9, comprising an organic group attached to the surface of the lithium that is derived from an aromatic diazonium salt optionally substituted with a functional group.

11. 11. The functionalized lithium anode of claim 10 comprising a substituted phenyl group bonded to a surface of the lithium.

12. The functionalized lithium anode according to any one of claims 9 to 11 is used in Li-S cells, Li-ion cells or Li-O cells. 2 Use in cells selected from cells.

13. A Li-S cell, Li-ion cell or Li-O cell comprising the functionalized lithium anode according to any one of claims 9 to 11. 2 The cell selected from the cell.

14. Use of the cell of claim 13 in an electronic device.

15. An electronic device comprising the cell of claim 13.

Citation Information

Patent Citations

  • Rechargeable alkaline metal and alkaline earth electrodes having controlled dendritic growth and methods for making and using the same

    US20120295149A1

  • Chemically modified reduced graphene oxide as a separator material in sulfur-containing batteries

    WO2015088451A1

  • Lithium electrodes for lithium-sulphur batteries

    WO2016083271A1